In vitro Release Kinetics Study of Ambroxol Hydrochloride Pellets Developed by Extrusion Spheronization Technique Followed by Acrylic Polymer Coating - Ahmed, Ishtiaq; Roni, Monzurul Amin; Kibria, Golam; Islam, Muhammad Rashedul; Jalil, Reza-ul (Dhaka University Journal of Pharmaceutical Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The aim of the present study was to investigate the effect of Ammonio Methacrylate Copolymer Dispersion Type A (Eudragit RL 30 D) and Ammonio Methacrylate Copolymer Dispersion Type B (Eudragit RS 30 D) combination in different weight ratios on the release kinetics of Ambroxol Hydrochloride from coated pellets. Microcrystalline cellulose, lactose, maize starch, hydroxypropyl methylcellulose and the drug was incorporated in the nuclei prepared by Extrusion-Spheronization technique which was coated with Eudragit RL 30D and Eudragit RS 30D in 1:1,1:1.5,1:2,1:2.5 and 1:3 ratios. The in vitro dissolution studies were carried out in 0.1N HCl for 1 hour followed by phosphate buffer (pH 6.8) for 11 h with USP dissolution apparatus Type-II. Drug release decreased with increasing amount of Eudragit RS 30 D in all cases. The drug release followed first order and Higuchi release kinetics. The Korsmeyer plot revealed n=0.50-0.61 or non-Fickian transport mechanism for drug release. From one way ANOVA it was found that the ratio of binary polymer mixer had significant (p < 0.05) effect on drug release. Key words: Aqueous coating, Eudragit, release kinetics, pellet, extrusion-spheronization Â  DOI = 10.3329/dujps.v7i1.1222 Dhaka Univ. J. Pharm. Sci. 7(1): 75-81, 2008 (June)